2019
DOI: 10.1111/joa.12940
|View full text |Cite
|
Sign up to set email alerts
|

Return of the intestinal loop to the abdominal coelom after physiological umbilical herniation in the early fetal period

Abstract: The intestine elongates during the early fetal period, herniates into the extraembryonic coelom, and subsequently returns to the abdominal coelom. The manner of herniation is well‐known; however, the process by which the intestinal loop returns to the abdomen is not clear. Thus, the present study was designed to document and measure intestinal movements in the early fetal period in three dimensions to elucidate the intestinal loop return process. Magnetic resonance images from human fetuses whose intestinal lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…Soffers et al (2015) addressed the development of the whole intestine and concluded that the intestine does not "rotate" but "slides" from the umbilical coelom into the abdominal cavity 7 . Recently, Nagata et al (2019) studied the return of intestinal loops after PUH, proposing an alternative "wrapped model" instead of the classical "rope model" 8 .…”
mentioning
confidence: 99%
“…Soffers et al (2015) addressed the development of the whole intestine and concluded that the intestine does not "rotate" but "slides" from the umbilical coelom into the abdominal cavity 7 . Recently, Nagata et al (2019) studied the return of intestinal loops after PUH, proposing an alternative "wrapped model" instead of the classical "rope model" 8 .…”
mentioning
confidence: 99%
“…Such growth proceeded regardless of the phases of herniation. In our previous study, the ventral‐dorsal height of the abdomen (abdominal height) was an exception, as there was increased abdominal height between the transition phase and return phase (Nagata et al, 2019).…”
Section: Discussionmentioning
confidence: 92%
“…Drastic and dynamic change occurs between the herniation phase and return phase of IL. The elongated IL herniated in the extraembryonic coelom, which promptly returns in the abdominal coelom in the fetal stage at approximately 40 mm (Kim et al, 2003; Mall, 1899; Nagata et al, 2019; Snyder Jr & Chaffin, 1952). Prompt changes in both the abdominal and umbilical compositions as well as volume should occur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The delay in innervation may correspond with the rapid growth of the midgut resulting in the formation of loops (Soffers et al ., 2015; Ueda et al ., 2016). In agreement, the ganglionic cells of the intrinsic ENS begin to form the myenteric plexus at ~CS22 (Okamoto and Ueda, 1967, Fu et al ., 2004, Wallace and Burns, 2005), just prior to intestinal return and resolution of the hernia (Soffers et al ., 2015; Nagata et al ., 2019). Furthermore, it has been reported, however, that the mitotic index in the ileocaecal region of 11–12 weeks old foetuses was still ~2‐fold higher than in the oesophagus or hindgut (Vaos, 1989), while enteric neurons were less developed in the ileum than in adjacent parts of the gut (Tam, 1986).…”
Section: Discussionmentioning
confidence: 99%